2002
DOI: 10.1046/j.1525-1594.2002.06975.x
|View full text |Cite
|
Sign up to set email alerts
|

Chordal‐Sparing Mitral Valve Replacement Using Artificial Chordae Tendineae for Rheumatic Mitral Stenosis: Experience of the “Oblique” Method

Abstract: Chordal-sparing mitral valve replacement (CSMVR) has been proven to be beneficial for postoperative left ventricular (LV) function. In patients with mitral stenosis, however, diseased chordae tendineae (CT) often have to be replaced using artificial CT to achieve CSMVR. Previously, we reported that resusupension of artificial CT in an oblique direction enhances systolic LV function. Among 40 consecutive patients with mitral valve replacement (MVR), 17 (4 men and 13 women; mean age 66.5 years) with rheumatic mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…They showed that MVR with preservation of chordae tendineae can be expected to have a beneficial effect on postoperative LV performance in mitral stenosis patients. In another study, Soga and associates 13 reported the results of chordal-sparing MVR performed by using artificial chordae in 17 patients who presented with rheumatic mitral stenosis and preserved LV systolic function. At 14 months' follow-up, the LV dimensions and the LVEFs of patients who had undergone chordal-sparing MVR were comparable to their preoperative levels.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They showed that MVR with preservation of chordae tendineae can be expected to have a beneficial effect on postoperative LV performance in mitral stenosis patients. In another study, Soga and associates 13 reported the results of chordal-sparing MVR performed by using artificial chordae in 17 patients who presented with rheumatic mitral stenosis and preserved LV systolic function. At 14 months' follow-up, the LV dimensions and the LVEFs of patients who had undergone chordal-sparing MVR were comparable to their preoperative levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, experimental data have shown that interruption of the continuity between the mitral annulus and papillary muscles leads to deterioration of LV systolic function even in normal hearts. 13,21 Therefore, preservation of the subvalvular apparatus could also optimize postoperative LV systolic function in mitral stenosis patients. Of several studies grounded on this assumption, most have shown improvement in postoperative outcome through subvalvular-apparatus preservation, as did our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations